A Prototype of Parking Space Information System based on Image Processing - Aaron Abel; Suci Aulia; Dadan Nur Ramadhan; Sugondo Hadiyoso (Universitas Syiah Kuala, 2021)
An automatic parking system has been proposed to make the car parking process more efficient in terms of time and cost. The absence of information on the position of the parking lot makes the car driver take longer to find it. In multi-story parking lots, officers cannot constantly monitor the available parking conditions directly, so prospective parking users do not know the position of the open parking space. In addition, many parking lots use automatic door latch, but no parking space information display. Parking system automation can be based on hardware, software, or a combination of hardware and software. To the best of our knowledge, no software-based framework is entirely used on this system. Therefore, this study proposes an automatic parking system based on camera sensors and software, which is combined into an information system. The proposed method uses simple morphological operations. Based on the test results, the detection accuracy achieved is 100% with a light intensity of 3 lux, 15 lux, 30 lux, 60 lux, 120 lux, and 250 lux. The average processing time is 1.59 seconds. From this study, it is hoped that this prototype can be tested on relevant environmental conditions so that the prototype can be implemented in parking lots.